PEMBERDAYAAN PETANI OLEH PEMERINTAH KABUPATEN SIAK DI KAWASAN AGRO WISATA KECAMATAN BUNGA RAYA TAHUN 2017-2018 - Romulus Sitorus; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The agricultural and tourism sectors play a strategic role in the development of the national economy. Not only as a provider of foodstuffs, industrial raw materials, feed, labor absorbers, sources of livelihoods and sources of foreign exchange, agriculture and tourism also serves as a driver of regional development and at the same time a driver of populist economic development.. These strategic roles are in line with the national economic development goals of improving the welfare of Indonesians, accelerating economic growth, reducing poverty, providing jobs, and maintaining the balance of natural resources and the environment. Seeing the condition of Indonesian people who are mostly agrarian people and also many interesting tourist attractions so that potentially in the economic development of the community one of them, by showing by most of their income comes from agriculture such as food crops and plantations.Community empowerment is an effort to develop the independence and welfare of the community by improving knowledge, attitudes, skills, behaviors, abilities, awareness, and utilizing resources through the determination of policies, programs, activities, and mentoring in accordance with the essence and priority of community needs. The formulation taken is How empowerment is done by the Siak District Government in empowering farmers who are in the agrotourism area of Bunga Raya Subdistrict in 2017-2018 and What is an inhibitory factor in empowering farmers in Bunga Raya Subdistrict.The purpose of this research is the first to find out the empowerment conducted by the Siak Regency Government to farmers who are in the agrotourism area in 2017-2018. To know the inhibitory factors in empowering farmers in Bunga Raya Subdistrict. The research method used is Qualitative Research. This type of research is Descriptive Qualitative Location of this research in the Department of Agriculture Siak and agricultural areas Bunga Raya District. Data collection techniques by means of Interviews, Observations or observations and documentation studies. Data analysis techniques by qualitative descriptive method.The results of the research showed that in empowering farmers in Bunga Raya Subdistrict there are several ways that create the potential of the community Allows it to develop, Strengthen the potential of the community (Empowering) and To Prevent the Weak From Getting Weaker (Protecting). The factors that hinder farmers are divided into two, namely: There is no follow-up from the Government, especially the tourism office in conducting training on farmers living in agrotourism areas, the absence of guaranteed capital budgets to government farmers who are less able to bridge between farmers and buyers. External inhibitory factors Lack of activeness farmers in following the counseling conducted by the government through extension workers.Keywords: Empowerment of farmers, agrotourism areas, agricultural sector, enabling, protecting, empowering.